Effects of plant density on seed yield and it’s components of two pea (Pisum sativum L.) cultivars under rainfed condition in Sulaimani province - Ibrahim, Dayan Majeed; Mohamed, Shiren Jalal; Ahmed, Shilan Mahmood (Journal of Kerbala for Agricultural Sciences, 2019)
This study was carried out to investigate the response of two cultivars of pea (Markerbsen and Zuckerbsen) to three plant densities (20, 40, and 80 plant. m-2) under the rain fed condition in Sulaimani province, during the growing seasons of (2014-2015 and 2015-2016). RCBD in factorial experiments arrangement was used with three replications. The results showed no significant effects of cultivars, plant densities and their interaction on plant height, while, the cultivar of Zuckerbsen was significantly gave higher dry weight compared to Markerbsen and at lowest plant density (20 plant. m- 2) followed by (40 plant. m-2). Number of branches.plant-1, number of pods.plant-1, number of seeds.pod-1, number of seeds.plant-1, biological yield had not affected by both cultivars and plant densities. However, the highest and significant weight of seed, 1000 seed weight, harvest index (HI) were obtained in first growing season by Zuckerbsen cultivar at 20 plant. m-2 compared with Markerbsen cultivar at (40 and 80 plant. m-2) densities and second growing season . The highest seed yield was obtained by Zuckerbsen cultivar in both growing seasons at plant density of (80 plant. m-2) with value of 3159.95 kg. ha-1) in first growing season and value of (2873.65 kg. ha-1) in second growing season followed by Markerbsen cultivar in first growing season with value of (2599.52 kg.ha-1) at 80 plant. m-2) compared to other plant densities this mean both cultivar performed better in first growing season with higher rainfall and lower temperature during pod development compared to second growing season. This study suggested Zuckerbsen cultivar and plant density of 80 plant. m-2 for Sulaimani province.